PENGARUH VARIASI AGREGAT KASAR PENYUSUN BETON POROUS TERHADAP KUAT TEKAN DAN POROSITAS BETON - Irene Vista Simanjuntak; Sudarno P Tampubolon (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2022)
The continued use of traditional concrete has resulted in a thicker layer of waterproofing, preventing rainwater from entering the ground and increasing surface run off. As a result, the water table drops during the rainy season, and flooding occurs. One of the innovations to anticipate or overcome these problems is using renewable materials such as aerated concrete. Permeable concrete pavements are intended to reduce puddles on the street. By omitting fine aggregate, porous concrete is simple, lightweight concrete. The interconnected cavities result in a high level of porosity. Porous concrete usually has little to no fine aggregate and enough cement paste to coat the coarse aggregate's surface. Due to the increased porosity, the compressive strength of un-sanded concrete is lower than that of conventional normal concrete. Sand-free concrete has much lower tensile and flexural strength than conventional concrete. In this study, two coarse aggregates with nominal maximum sizes of 12.5 mm and 6.7 mm were used as split rocks with weights of 1.123 kg/m3 and 2.63 kg/m3, respectively. Hence, a FAS of 0.35 and a water volume of 0.35 kg using Portland cement type 1 with a quantity of 389.6 kg/m3. The test object is a concrete cylinder with a diameter of 80 mm and a height of 16 mm. After immersing the specimen in a tub of water, each mixture has three specimens.